Development and pre-clinical evaluation of HIV-1 vaccines - Mbewe-Mvula, A (2017)
Infants born to HIV-1 positive mothers are at risk of acquiring the infection through pro-longed breastfeeding due to the presence of HIV-1 cell-free RNA and cell-associated DNA in breast milk. However, there is limited focus on vaccines to prevent mother-to-child transmission (MTCT) via breastfeeding. Mycobacterium tuberculosis (M. tuberculosis) the causative agent of Tuberculosis (TB) is the most common cause of AIDS-related deaths. Most infants in Africa receive Bacillus Calmette-Guérin (BCG) at birth or soon after birth and it is the only licensed vaccine for TB. The development of a dual platform vaccine against HIV-1 and TB would be a logical effort to combat these two deadly diseases. Thus, rBCG expressing an HIV-1 derived immunogen may induce HIV-1 responses at birth and these responses can be boosted at adolescence, by a heterologous vector such as modified vaccinia Ankara (MVA) or Chimpanzee adenovirus serotype 63 (ChAdV63). In the first study, I assessed BCG-based vaccines derived from BCG Danish SSI-1331 (BCG1331), expressing an HIV-1 immunogen HIVconsv either by an episomal plasmid (BCG.HIVconsv401epi) or integrated into the BCG chromosome (BCG.HIVconsv401int) in a prime-boost regimen. BALB/c mice were immunised with the different prime-boost regimens. rBCG alone was unable to induce detectable HIV-1-specific T-cell responses, however, when used in a prime-boost strategy, elevated HIV-1-specific T-cell responses were observed. In the second study, I aimed to construct marker-less mycobacterium-vectored HIV-1 vaccines using the operator-repressor titration (ORT®) system as an alternative system for antibiotic resistance gene free vaccines. This rBCG vaccine would express the HIVconsv immunogen. I first constructed plasmids carrying the lac operator lacO and tetracycline operator tetO to enable use in ORT Escherichia coli (E.coli) and Mycobacterium strains, respectively. The ORT system was successful in E. coli and not in mycobacterium. I also constructed plasmids carrying mycobacterium essential genes that would allow for genetic manipulation in Mycobacterium and the use of ORT in mycobacterium. Although the plasmid construction was successful, in the end, genetic manipulations in Mycobacterium and the production of an ORT based BCG (ORT-VAC) was not successful. Finally, I evaluated the immunogenicity of conventional DNA plasmid pTH.HIVconsv compared to Semliki Forest virus replicon DREP.HIVconsv in rhesus macaques. Immunisations were done in a prime-boost strategy with heterologous vectors MVA or ChAdV63 delivering the same immunogen, HIVconsv. It was found that DREP.HIVconsv which was at least 20-fold lower dose than pTH.HIVconsv was capable of inducing comparable T-cell responses and in some experiments, the responses were superior to the conventional DNA plasmid pTH.HIVconsv.